Attention and executive functions in a rat model of chronic epilepsy. Issue 5 (22nd February 2014) - Faure, Jean‐Baptiste; Marques‐Carneiro, José E.; Akimana, Gladys; Cosquer, Brigitte; Ferrandon, Arielle; Herbeaux, Karine; Koning, Estelle; Barbelivien, Alexandra; Nehlig, Astrid; Cassel, Jean‐Christophe
Summary: Objective: Temporal lobe epilepsy is a relatively frequent, invalidating, and often refractory neurologic disorder. It is associated with cognitive impairments that affect memory and executive functions. In the rat lithium‐pilocarpine temporal lobe epilepsy model, memory impairment and anxiety disorder are classically reported. Here we evaluated sustained visual attention in this model of epilepsy, a function not frequently explored. Methods: Thirty‐five Sprague‐Dawley rats were subjected to lithium‐pilocarpine status epilepticus. Twenty of them received a carisbamate treatment for 7 days, starting 1 h after status epilepticus onset. Twelve controls received lithium and saline. Five months later, attention was assessed in the five‐choice serial reaction time task, a task that tests visual attention and inhibitory control (impulsivity/compulsivity). Neuronal counting was performed in brain regions of interest to the functions studied (hippocampus, prefrontal cortex, nucleus basalis magnocellularis, and pedunculopontine tegmental nucleus). Results: Lithium‐pilocarpine rats developed motor seizures. When they were able to learn the task, they exhibited attention impairment and a tendency toward impulsivity and compulsivity. These disturbances occurred in the absence of neuronal loss in structures classically related to attentional performance, although they seemed to better correlate with neuronal loss in hippocampus. Globally, rats that received carisbamate and developed motor seizures were as impaired as untreated rats, whereas those that did not develop overt motor seizures performed like controls, despite evidence for hippocampal damage. Significance: This study shows that attention deficits reported by patients with temporal lobe epilepsy can be observed in the lithium‐pilocarpine model. Carisbamate prevents the occurrence of motor seizures, attention impairment, impulsivity, and compulsivity in a subpopulation of neuroprotected rats. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here .